Media competence in primary education in the Spanish context (Educação e Pesquisa, 2016)
For almost four years, a large group of Spanish researchers from over twenty universities in Spain has been studying the population’s levels of competence in media in order to promote media literacy programs in schools and non-formal settings. The concept of media literacy encompasses our skills and knowledge on the media and can be measured by six dimensions: language, technology, production and programming, reception and audiences, ideology and values, and finally aesthetics. This descriptive study explores the extent of those competences in the context of fourth grade students, aged nine and ten years in Spain. It was necessary to design an online questionnaire whose content and design was adapted to their age, to know whether the 581 participants in the sample are competent from a media point of view. The results show that nothing is what it seems. Despite what one might assume, further training in media is necessary for students of this compulsory education level. Therefore, media literacy programs are needed in schools and households.